Local field effect influenced third-order optical nonlinearity of whole visible transparent chalcogenide glass ceramics. Issue 8 (1st June 2019) - Sun, Tingting; Chen, Feifei; Lin, Changgui; Xue, Xuning; Yang, Yinwei; Dai, Shixun; Zhang, Xianghua; Ji, Wei
Abstract: In this work, whole visible transparent chalcogenide glass ceramics (ChGCs) were prepared by heat treating a chalcohalide glass (with a molar composition of 20GeS2 -35Ga2 S3 -45CsCl, GGC) for different time, and the formation of nano-crystals (NCs) belonging to the Ga2 S3 phase was identified. The femtosecond Z-scan technique was employed to observe, variations in the third-order optical nonlinearity (TONL) properties, especially the nonlinear refractive behaviour, due to the appearance of the Ga2 S3 NCs in the GGC glass network. The experimental results show that both sign and magnitude of the nonlinear refractive index ( n 2 at 800 nm) changed as a result of the local field effect generated by the size-confined Ga2 S3 NCs. The maximum n 2 value obtained from the Ga2 S3 NCs was over 4 times that of the base glass and over 230 times to that of silica glass.